Pengaruh Gaya Kepemimpinan Station Manager dan Sistem Reward Terhadap Kepuasan Karyawan pada Ground Staff Bandar Udara Internasional Yogykarta - Luthfi Zakiyyatussani; Arif Fakhrudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine the effect of Station Manager leadership style and reward system on employee satisfaction in Ground Staff at Yogyakarta International Airport. The study used a quantitative method with a causal associative approach. The population in this study amounted to 40 airline Ground Staff at Yogyakarta International Airport, with a sampling technique using saturated sampling or census so that the entire population was used as a research sample. Data collection was carried out by distributing questionnaires using a Likert scale. Data were analyzed using validity tests, reliability tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination (R²) with the help of the SPSS version 22 program. The results showed that leadership style had a positive and significant effect on employee satisfaction with a significance value of 0.007 <0.05. Meanwhile, the reward system did not have a significant effect on employee satisfaction with a significance value of 0.148 > 0.05. However, simultaneously, leadership style and reward system had a significant effect on employee satisfaction with a significance value of 0.000 <0.05. The coefficient of determination (R²) of 0.466 indicates that leadership style and reward systems explain 46.6% of employee satisfaction, while the remaining 53.4% ​​is influenced by factors outside the study. This study demonstrates that the implementation of an effective leadership style plays a significant role in increasing employee satisfaction among Ground Staff at Yogyakarta International Airport.